Impact of 12-Week Aerobic Dance and Weight Training on Body Composition and Fitness of Sedentary Women - Melchisedec Kiruba; Natarajan Priyadarshini; Elumalai Saravanan; Mohansundar Sankaravel; Ethiraj Balaji (Слобожанський науково-спортивний вісник)
Background and study aim: Weight training and aerobic dancing have positive effects on women who are sedentary. Nonetheless, less emphasis has been placed on the combined effects of using two distinct training modalities in one session. The need to look into these training techniques is indicated by this research gap. The purpose of this research aims to establish whether combining aerobic dance with weight training provides an effective fitness enhancement method that leads to better lifestyle health for sedentary women.